"For all the Alterations which I made were in the first Act": Authorship and Editorial Interference in Aphra Behn's The Younger Brother (1696). Issue 3 (2nd July 2020) - Hogarth, Alan James; Evans, Mel
ABSTRACT: In his preface to Behn's posthumously published play, The Younger Brother (1696), Charles Gildon, who secured the play's performance and publication, makes claims to editorial interference in the first Act, and specifically Act I, scene 2. Given Gildon's reputation during his lifetime as a commercially driven hack-writer and sometime forger, speculation abounds about the nature of his involvement with the play. Such questions range from how much of The Younger Brother, if any, can reliably be attributed to Gildon, to whether the whole play is in fact a forgery that sought to capitalise on Behn's continuing posthumous popularity. This study brings a new approach to these questions of authorship and editorial practices. It uses computational stylistic methods to measure the possible contributions of Gildon and Behn to The Younger Brother, and considers what the results might mean in light of previous critical perceptions of Gildon, and the status of the author in the late seventeenth century.